Effect of sowing dates on confectionery traits of groundnut cultivars: Effect of sowing dates on confectionery traits of groundnut cultivars - HARPUNEET KAUR; VIRENDER SARDANA; D N YADAV; M S ALAM; PUSHP SHARMA (Journal of Oilseeds Research, 2020)
Groundnut being a rich source of quality oil, protein and minerals, is considered as a potential crop to overcome protein-energy malnutrition. Its demand for use in confectionery is fast increasing. A field experiment was conducted with 4 sowing dates and 4 spanish bunch cultivars in 2018. Sowing period of 25th February to 10th March offered better environment for test cultivars. Cultivars J-87 and SG-99 produced bolder size kernels with higher protein content whereas, J-87 and TG-37A had higher reducing sugar content in kernels. TG-37A also had lower fat and total solids in milk than other cultivars.